Osteoporosis: Connection to urologic health - Cheung, Angela M. (Canadian Urological Association Journal, 2014)
Men with prostate cancer are often treated with androgen deprivation therapy (ADT), which is associated with reduced bone mineral density (BMD) and a higher risk for fractures. Maintenance of optimum bone health throughout the natural course of prostate cancer is an important aspect in the management of this patient population. Bone targeted therapies such as bisphosphonates and the RANK ligand inhibitor denosumab have been demonstrated to reduce skeletal-related events in patients with metastatic cancer, while denosumab has also been shown to reduce the risk of fracture in men undergoing ADT for prostate cancer.